The association between ferritin levels and all-cause mortality in stroke patients - Xia, Xuefen; Liu, Jiongjiong; Fang, Wenqiang; Chen, Zhibo; Wang, Jie; Xu, Huiqin (Frontiers in Neurology, 2024)
Purpose: The purpose of study was to describe the association between ferritin and all-cause mortality of cases with stroke.Methods: Clinical data derived from Multiparameter Intelligent Monitoring in Intensive Care were analyzed. The primary endpoint was 30-day mortality. The potential prognostic roles of Ferritin L were analyzed by Cox proportional hazard models. The independent prognostic roles of Ferritin L in the cases were analyzed by smooth curve fitting.Results: Concerning 30-day mortality, the HR (95% CI) for a high Ferritin (≥373) was 1.925 (1.298, 2.854; P = 0.00113), compared to a low ferritin (< 373). After adjusting for multiple confounders, the HR (95% CI) for a high Ferritin (≥373) was 1.782(1.126, 2.820; P = 0.01367), compared to a low Ferritin (< 373). A non-linear association between Ferritin and 30-day mortality was found. Using recursive algorithm and two-piecewise linear regression model, IP (inflection point) was calculated, which was 2204 On the left side of the IP, there was a positive relationship between Ferritin and 30-day mortality, and the effect size, 95% CI and P value were 1.0006 (1.0004, 1.0009) P<0.0001, respectively. On the right of the IP, the effect size, 95% CI and P value were 1.0000 (1.0000, 1.0000) and 0.3107, respectively.Conclusions: Ferritin was associated with increased risk of stroke; it is important to further examine the association if the increased uric acid would increase the outcome of stroke in a longitudinal study. The non-linear relationship between Ferritin and all-cause mortality of stroke was observed. Ferritin was a risk factor for the outcome of stroke when ferritin was < 2204.